Electric Aircraft: Alternative Power Sources - Hjärpe, Victor; Hobbenschot, Thijs; Hedlund, Marcus; Hjort, Viktor (TMAL02 Expert Conference, 2020)
The development of electric aircrafts is going on to a great extent today. Many large well-known companies in the aerospace industry are working hard to achieve functional and useful aircrafts that can handle the demands required for longer and more efficient air travel. This project examines how electric aircraft work today and the limitations that exist. How they can be developed and function in the future. The aim of this project is to understand how electric aircrafts work and why they are not used today, as well as what is required for them to function as commercial aircrafts in the future.